Discovery of 2-aryloxy-4-amino-quinazoline derivatives as novel protease-activated receptor 2 (PAR2) antagonists. Issue 24 (15th December 2015) - Cho, Nam-Chul; Cha, Ji Hyoun; Kim, Hyojin; Kwak, Jinsook; Kim, Dohee; Seo, Seung-Hwan; Shin, Ji-Sun; Kim, TaeHun; Park, Ki Duk; Lee, Jiyoun; No, Kyoung Tai; Kim, Yun Kyung; et al.
Graphical abstract: Abstract: Protease-activated receptor 2 (PAR2 ) is a member of G protein-coupled receptor and its activation initiates diverse inflammatory responses. Recent studies suggest that antagonists of PAR2 may provide a novel therapeutic strategy for inflammatory diseases. In this study, we have developed a series of 2-aryloxy-4-amino-quinazoline derivatives as PAR2 antagonists and examined their effects against LPS-induced inflammatory responses in RAW 264.7 macrophages. Among these derivatives, compound2f displayed the greatest antagonistic activity with the IC50 value of 2.8 μM. Binding modes of the newly identified PAR2 antagonists were analyzed by molecular docking using IFD/MM-GBSA methods in the putative binding site of PAR2 homology model. Moreover, 2f demonstrated significant inhibitory effects on the LPS-activated pro-inflammatory mediators including nitric oxide (NO), prostaglandin E2 (PGE2 ), interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) through the regulation of various intracellular signaling pathways involving nuclear factor-κB (NF-κB), activator protein 1 (AP-1) and the mitogen-activated protein kinases (MAPK). Furthermore, administration of2f significantly reduced the mortality of LPS-induced sepsis in mice. These results provide useful insights into the development of novel PAR2 antagonists with anti-inflammatory activity in vitro and in vivo.